Degradation of bioplastics in organic waste by mesophilic anaerobic digestion, composting and soil incubation. (October 2021) - Cucina, Mirko; De Nisi, Patrizia; Trombino, Luca; Tambone, Fulvia; Adani, Fabrizio
Graphical abstract: Highlights: Assessment of bioplastic degradation during mesophilic treatments at pilot scale. Bioplastics degraded by 17 % and 30 % total solids after AD and AD plus composting. Compost showed high bioplastic content (18 % TS) and did not meet legal limits. Starch-based bioplastics degrades faster than polylactic acid polymer in soil. Bioplastics in soil degrade completely in 8–9 years according to calculated kinetic. Abstract: The aim of the study was to assess the effects of high concentrations (10 % w/w, data projected for 2030) of commercial bioplastics, i.e. starch based shopping bags (SBSB) and polylactic acid (PLA) tableware, in the organic fraction of municipal solid wastes (MSW) on compost quality obtained by pilot-scale dry mesophilic anaerobic digestion and subsequent composting of the digestate. After the biological processes, 48.1 % total solids (TS) of SBSB and 15 % TS of PLA degraded, resulting in a high bioplastics content (about 18 % TS) in compost. Subsequent compost incubation in soils indicated that bioplastics degraded by pseudo-zero order kinetics (0.014 and 0.010 mg C cm −2 d -1 for SBSB and PLA, respectively), i.e. complete degradation was expected in 1.6 years (SBSB) and 7.2 years (PLA), confirming the intrinsic biodegradability of bioplastics. Nevertheless, enhancing the rate and amount of bioplastics degradation during waste management represents a goal to decrease the amount of bioplastics reaching the environment.